Transcription of African music from silent film: theory and methods - Kubik, Gerhard (International Library of African Music, 1972)
Most films on music and dance which are used for ethnomusicological research purposes are not research films, but documentaries. Research film in ethnomusicology has undergone important development in the last ten years. It can be distinguished from plain documentary in that it records intentionally those aspects of the event which later will allow the researcher to answer certain preconceived questions
Keywords: Research; Graphic notation (Music); Ethnographic films; Africa; Ethnomusicology; Arrangement (Music); African Music